APRESIASI DOSEN TERHADAP FABEL - Haryadi, Haryadi (Jurnal Cakrawala Pendidikan, 2015)
Societies ofold appreciated animal fables highly. They used such fables as means ofentertainment and education. Along with developments in science and technology, society’s appreciation offables has started to change. As part ofmodem society, university lecturers have also been in lesser or greater degrees contaminated withnewviewson such fables. What their appreciation ofsuch fables is like would be analyzed in this writing. This article is based on the results ofa research on apopulation consisting ofteachers at Universitas Negeri Yogyakarta (UNY). Ninety ofthem have been selected for the research by means ofsimple random sampling. The research instrument used has been a questionnaire containing twenty questions concerning relevant knowledge and appreciative activities. The data have been analyzed by means ofa descriptive quantitative technique. The research has yielded the conclusion that university teachers appreciation ofanimal fables as seen from indicators ofliterary appreciation is good. Mastery ofknowledge, receptive activity, and communication to others are categorized ’good’ while documentative and productive ctivities are categorized ’fair’. Meanwhile, it turns out that gender, educational level, academic position, dan residence do not make a difference in their level of appreciation of such fables.